2014
DOI: 10.1027/1015-5759/a000175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Wording Effect and Psychometric Properties of the Kid-KINDL

Abstract: Quality of life (QoL) instruments for children provide an important health index for school healthcare professionals to understand students’ overall health status. We investigated the psychometric properties of the Chinese version of the widely used Kid-KINDL and reported on the wording effect of its positively and negatively worded items. A convenience sample of 8- to 12-year-old students (n = 443) completed the Kid-KINDL; 89 of them completed it again 7–14 days later. The internal consistency was satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 28 publications
6
53
3
1
Order By: Relevance
“…The internal consistency in our study (α = .59–.86) corresponds to the previous data from Germany (α = .59–.86) [5], Norway (α = .67–.89) [6], and Serbia (α = .50–.85) [7]. Our findings are also comparable to the Chinese version of the child-reported Kid-KINDL (α = .52–.87) [10]. In addition, the four subscales with α < .7 in the current study had low values of subscale internal consistency that was also found in other studies [5, 7, 10].…”
Section: Discussionsupporting
confidence: 88%
“…The internal consistency in our study (α = .59–.86) corresponds to the previous data from Germany (α = .59–.86) [5], Norway (α = .67–.89) [6], and Serbia (α = .50–.85) [7]. Our findings are also comparable to the Chinese version of the child-reported Kid-KINDL (α = .52–.87) [10]. In addition, the four subscales with α < .7 in the current study had low values of subscale internal consistency that was also found in other studies [5, 7, 10].…”
Section: Discussionsupporting
confidence: 88%
“…Items 26 and 30 are new to the SQLS-R4 and have relatively low factor loadings (<0.3) in the vitality construct and psychosocial construct, in previous studies [ 6 , 13 ]. The wordings of these two new items may still be under development, which might contribute to their unstable psychometric properties [ 24 ]. Another possible reason is that the participants in our study were institutionalized and may have had limited social lives as well as happy feelings.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the data-model fit for the five models, we used the χ 2 test and four additional indices: the comparative fit index (CFI), Tucker-Lewis index (TLI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR). The values of the CFI and TLI were > 0.9 [ 22 ], and those of the RMSEA and SRMR were < 0.08, which suggests that the data-model fit is acceptable [ 23 , 24 ]. Moreover, to compare the five models, Akaike's information criterion (AIC) and expected cross-validation index (ECVI) were consulted; smaller values indicate a better fit [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because three misfit items in this study were negatively worded, we tentatively concluded that substance abusers may not have sufficient intact cognitive function to interpret the three items as they were intended to be understood. Negatively worded items have a wording effect that biases the evaluation of the extracting constructs of QoL instruments [ 31 ], especially in the case of people without sufficient cognitive ability. Therefore, the underlying constructs, such as the Physical and Psychological domains, may be affected by the negatively worded items [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%